"Il est à craindre que l’anglais ne prenne une place prépondérante”: la posición de las autoridades francesas respecto a las políticas lingüísticas de la UE - Martín Martín-Mora, Concepción; Jiménez-Salcedo, Juan (Anales de Filología Francesa, 2024)
This paper examines the status of the French language in the European Union, particularly in recent years. To this end, a corpus of documents issued by French organisations and authorities and those linked to the French-speaking world, such as the Government of the French Republic and its institutions and the International Organisation of La Francophonie, has been compiled. These documents show the position of French, highlight the advance of English, and propose measures to reverse the situation. The corpus has been analysed using an inductive methodology. Among the results obtained, a significant decline in the use of French, both in external and internal communication, can be highlighted. The French authorities have taken action to try to solve this issue, but they do not seem to have achieved the expected results.